Knowledge hubs and knowledge clusters: Designing a knowledge architecture for development - Hans-Dieter Evers (University of Bonn, Center for Development Research (ZEF), 2008)
With globalisation and knowledge-based production, firms may cooperate on a global scale, outsource parts of their administrative or productive units and negate location altogether. The extremely low transaction costs of data, information and knowledge seem to invalidate the theory of agglomeration and the spatial clustering of firms, going back to the classical work by Alfred Weber (1868-1958) and Alfred Marshall (1842-1924), who emphasized the microeconomic benefits of industrial collocation. This paper will argue against this view and show why the growth of knowledge societies will rather increase than decrease the relevance of location by creating knowledge clusters and knowledge hubs. A knowledge cluster is a local innovation system organized around universities, research institutions and firms which intend to drive innovations and create new industries. Knowledge hubs are localities with a knowledge architecture of high internal and external networking and knowledge sharing capabilities. Countries or regions form an epistemic landscape of knowledge assets, structured by knowledge hubs, knowledge gaps and areas of high or low knowledge intensity. The paper will focus on the internal dynamics of knowledge clusters and knowledge hubs and show why clustering takes place despite globalisation and the rapid growth of ICT. The basic argument that firms and their delivery chains attempt to reduce transport (transaction) costs by choosing the same location is still valid for most industrial economies, but knowledge hubs have different dynamics relating to externalities produced from knowledge sharing and research and development outputs. The paper draws on empirical data derived from past and ongoing research in the Lee Kong Chian School of Business, Singapore Management University and in the Center for Development Research (ZEF), University of Bonn.
urn:nbn:de:0202-20080911278
Keywords: 330; knowledge and development; knowledge governance; innovation; space; Vietnam; Straits of Malacca